Cutaneous Basal Cell Carcinoma with Bone Metastases: An Orthopaedic Case Report - Brianna R. Fram; John Strony; Geetha Jagannathan; Scot A. Brown (Case Reports in Orthopedics)
Basal cell carcinoma (BCC) is the most common skin cancer, and its incidence is increasing. Though metastatic BCC (mBCC) is uncommon, the literature demonstrates a 0.0028%-0.55% rate of metastasis. We report on a patient treated at our institution who was found to have mBCC with osseous metastases. To our knowledge, this is the first report of mBCC in the orthopaedic literature. Orthopaedic oncologists should consider mBCC in patients diagnosed with carcinoma of unknown origin, with a known history of BCC, or individuals with light skin pigmentation and age 50 or greater. This can help clinicians make the correct diagnosis and provide the appropriate treatment.